Bimbingan dan Konseling Islam dengan Acceptance And Commitment Therapy (ACT) terhadap Seorang Ibu yang Minder Mempunyai Anak Cacat Fisik di Desa Tambakromo Kecamatan Cepu (Jurnal Bimbingan dan Konseling Islam, 2017)
The focus of this research is (1) What is the process of Islamic Guidance and Counseling with Acceptance and Commitment Therapy (ACT) for an inferior mother who has a physically handicapped child in Tambakromo Village, Cepu District? (2) What is the outcome of the Islamic Guidance and Counseling process with Acceptance and Commitment Therapy (ACT) for an inferior mother who has a physically handicapped child in Tambakromo Village, Cepu District? This study uses a qualitative method with a comparative descriptive approach. Data collection through observation, interviews, and documentation. Analysis is carried out to find out the process and results by comparing Islamic Guidance and Counseling between theory and field and comparing the client's condition before and after getting counseling in analyzing. In this study the counselor uses Acceptance and Commitment Therapy (ACT) which the counselor tries to help the client to accept the unpleasant thoughts / feelings that arise in him. Self-acceptance is very important to achieve a better life. The final results of the counseling process in this study were quite successful with a percentage of 70%, which results can be seen from the changes in the client's attitude or behavior that is not good began to get better.